2013
DOI: 10.1103/physrevlett.111.015501
|View full text |Cite
|
Sign up to set email alerts
|

Phase Diagram and Structural Diversity of a Family of Truncated Cubes: Degenerate Close-Packed Structures and Vacancy-Rich States

Abstract: Using Monte Carlo simulations and free-energy calculations, we determine the phase diagram of a family of truncated hard cubes, where the shape evolves smoothly from a cube via a cuboctahedron to an octahedron. A remarkable diversity in crystal phases and close-packed structures is found, including a fully degenerate crystal structure, several plastic crystals, as well as vacancy-stabilized crystal phases, all depending sensitively on the precise particle shape. Our results illustrate the intricate relation be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
172
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(187 citation statements)
references
References 45 publications
(70 reference statements)
15
172
0
Order By: Relevance
“…S1 and S2, and Table S4). Cubes densely pack into a simple cubic (SC) crystalline phase, with slight distortions in orientation for mildly truncated or rounded corners, or a plastic or crystalline FCC phase for high degrees of imperfection (20,(27)(28)(29)(30)(36)(37)(38). Indeed, a smaller zone of anisotropy was observed for cubes relative to octahedra and rhombic dodecahedra, consistent with the above hypothesis.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…S1 and S2, and Table S4). Cubes densely pack into a simple cubic (SC) crystalline phase, with slight distortions in orientation for mildly truncated or rounded corners, or a plastic or crystalline FCC phase for high degrees of imperfection (20,(27)(28)(29)(30)(36)(37)(38). Indeed, a smaller zone of anisotropy was observed for cubes relative to octahedra and rhombic dodecahedra, consistent with the above hypothesis.…”
supporting
confidence: 71%
“…S1, and Table S3). The dense packing of hard octahedra varies based on corner truncation or rounding (27)(28)(29), where body-centered cubic (BCC) or bodycentered tetragonal (BCT) crystalline phases are favored for truncated octahedra (26,29), and BCC or FCC plastic crystals are favored for rounded octahedra (28,30). In experimental systems, the hydrodynamic particle shape deviates from an ideal octahedron in favor of a BCC crystalline phase (13).…”
mentioning
confidence: 99%
“…Although simulation studies have mostly focused on investigating systems dominated by entropic effects through Monte Carlo simulations of hard-core particles [14]- [17], a few studies have also examined systems exhibiting enthalpic interactions using Molecular Dynamics (MD) simulations [18], [19]. The current work primarily aims to assess the role of enthalpic interactions on the selfassembly process, through the use of a coarse-grained model for the polyhedral NPs and explicit molecules to describe the fluids.…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments in experimental techniques [1][2][3][4][5][6][7] to controllably synthesize and manipulate polyhedral nanoparticles have fueled many theoretical [8,9] and simulation studies [10][11][12][13][14][15][16][17][18][19][20] to understand their packing and phase behavior. These building blocks have been shown to exhibit a rich phase behavior at finite osmotic pressures unveiling the presence of novel mesophases.…”
mentioning
confidence: 99%
“…An earlier study [21] on the miscibility trends of binary polyhedra mixtures revealed the importance of the relative size ratio of the components and of similarity in their mesophase behavior [10]. One of our aims is to identify shapes and sizes that favor the formation of entropic rotator mixtures.A family of truncated cubes, which is readily synthesizable [3,4], has been recently shown to exhibit a diverse set of phases [12]. Further, the kinetics of the disorderto-order transition for some members of this family has been shown to be substantially faster than that of hard spheres[23], making them appealing choices for applications requiring fast self-assembly.…”
mentioning
confidence: 99%